The effect of neckbands on the pairing status of Greater White-fronted Geese Anser albifrons - Babkina, Olga A.; Polikarpova, Diana R.; Litvin, Konstantin E.; Glazov, Petr M.; Loshchagina, Julia A.; Zaynagutdinova, Elmira M. (Wildfowl, 2025)
Individual marking is an essential method in avian ecological research, yet the potential ecological effects of tagging remain a concern. In this study, we investigated whether the presence of neckbands on Greater White-fronted Geese Anser albifrons affected the probability an individual was paired to another at a spring migratory stopover. Videos (15–30 min in duration) were recorded for 25 neck-banded and 25 randomly selected unmarked geese. From visual assessment of the behaviour of focal birds, pairing status (single or paired) was assessed for each. Our results found that over 70% of the neck-banded Greater White-fronted Geese were paired, and that there was no significant difference in pairing status between neck-banded and unmarked geese. Further studies with bigger sample sizes and using more advanced methods are needed to assess potential impacts of neckbands on the pairing status of Greater White-fronted Geese in greater detail.